Numerical investigation of air-staged combustion to reduce NOX emissions from biodiesel combustion in industrial furnaces. Issue 3 (June 2019) - Shen, Jiaxu; Li, Fashe; Li, Zhouhang; Wang, Huage; Shen, Yicheng; Liu, Zuowen
Abstract: In this paper, the combustion model of industrial furnace was established using numerical simulations. The application of air-staged combustion technology was used to solve the problem of high NOX emissions produced from the combustion of biodiesel in industrial furnaces. The simulation results were verified through experiments. The effects of secondary air distribution position ( Z sec), secondary air distribution ratio ( f sec) and the excess air coefficient (α) on the temperature field, incident radiation field and NOX concentration field distribution in the furnace were also studied. It was found that the simulated temperature and NOX concentration at the outlet of furnace were in good agreement with the experimentally determined results. When the staged combustion was not adopted, the NOX production in the furnace was at a high level. The average NOx concentration at the exit of the furnace was 0.000538 kg/m 3 . With the introduction of the staged ventilation technology, the lowest NOX production was 0.000276 kg/m 3, the best reduction effect was 48.7%. The optimal two-air-staged combustion test conditions were included Z sec of 50%, f sec of 30%, and α of 1.15. Highlights: The air-staged combustion technology is applied to reduce emissions. With the introduction of air-staged technology, the optimum emission reduction is 48.7%. These optimum air-staged conditions are found to be: Z sec of 50%, f sec of 30%, and α of 1.15.